HUBUNGAN GAYA HIDUP DENGAN KUALITAS HIDUP PADA PENDERITA MASALAH KAKI DIABETIK - Sukhri Herianto Ritonga; Dinda Permata Julianda; Adi Antoni (Universitas Prima Indonesia, 2021)
An increasing number of people with diabetes globally results in an increasing number of complications from diabetes, such as diabetic foot problems. Diabetic foot problem is one of the complications that most causes a decrease in the quality of life in sufferers. The aim of this study was to determine the relationship between lifestyle with quality of life in people with type 2 diabetes with diabetic foot problems. This research uses quantitative research with a case-control design with a retrospective approach. The number of respondents in this study was 50 people using the purposive sampling technique. The measuring instrument used to assess lifestyle is the Fantastic Lifestyle Score, while to assess the quality of life (WHOQOL) BREF. The statistical test used is the chi-square test. In this study, the p-value was 0.044 (α= 0.05) so that statistically there was a relationship between lifestyle with quality of life. Based on the odds ratio, the value was 3.886 (95% CI, 1.191-12.681), meaning that respondents who had a bad lifestyle were 3.8 times more likely to have a bad quality of life. The results showed that lifestyle was significantly related to the quality of life, where the better the lifestyle, the better the quality of life. This research can also be an input for health workers to make health services an effort to increase knowledge about the lifestyle and quality of life of people with diabetes.